JOYFUL MATH IN DIGITAL CLASSROOM: SYSTEMATIC LITERATURE REVIEW PERAN TEKNOLOGI INTERAKTIF DALAM MEMBANGUN JOYFUL LEARNING DAN KETERLIBATAN SISWA PADA PEMBELAJARAN MATEMATIKA - Puspa Puspa; Atmalya Selita; Destia Angraini Putri Rahim; Yogi Fernando; Meria Ultra Gusteti; Asrina Mulyati; Widdya Rahmalina (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Objective: This study aims to systematically examine the role of interactive technologies in facilitating enjoyable learning experiences within digital mathematics classrooms. The primary goal is to address the global barriers to mathematics education, specifically the widespread issues of low student engagement and high levels of math anxiety, by identifying effective digital interventions. Methods: The study was conducted using a Systematic Literature Review (SLR) methodology. The researcher analyzed 50 selected peer-reviewed articles to explore the integration of dynamic software, educational games, and creative pedagogical strategies. The analysis focused on how these digital tools influence the learning environment and student interaction in a digital context. Results: Key findings indicate that interactive technologies act as essential catalysts in enhancing intrinsic motivation by fulfilling students' needs for autonomy, competence, and connectedness. Furthermore, these tools facilitate the visualization of abstract mathematical concepts, making them more accessible. The data shows that learning outcomes improve significantly when elements of fun are purposefully integrated with appropriate digital tools, rather than using technology as a mere substitute for traditional methods.